(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Preoperative fasting (POF) is a standard practice to reduce the risk of aspiration and related complications during anesthesia. However, prolonged fasting beyond recommended durations can lead to patient discomfort, dehydration, and metabolic disturbances. International guidelines recommend fasting for six hours for solids and two hours for clear fluids before anesthesia. This audit aimed to evaluate POF practices at Northwest General Hospital Peshawar (NWGH) and compare them with international recommendations. Methodology: This clinical audit included 218 adult patients undergoing elective surgery under general or spinal anesthesia at NWGH between August 1 and October 31, 2024. Pediatric, pregnant, emergency, and non-consenting patients were excluded. Data were collected using a structured, interviewer-administered questionnaire assessing demographic characteristics, knowledge of POF, fasting duration, sources of fasting instructions, and associated complications. Results: Among the 218 patients, 57.8% were male and 42.2% female. While 97.7% recognized the importance of POF, 56% were unaware of its primary purpose. Only 7% adhered to the recommended six-hour fasting duration for solids, while 43% fasted for 9-10 hours, and 8% exceeded 12 hours. For clear fluids, only 4% fasted for the recommended two hours, while 61% fasted for 7-8 hours. Prolonged fasting led to discomfort and metabolic issues. Discussion: The findings highlight significant deviations from recommended POF practices, with inconsistencies in patient education and institutional policies. Extended fasting negatively impacted patient well-being and surgical outcomes. Standardized educational interventions and policy updates are necessary to align practices with international guidelines. Conclusion: Prolonged POF remains prevalent at NWGH due to inconsistent guidelines and inadequate patient education. Updating institutional policies, enhancing provider training, and improving communication can optimize patient comfort and safety.